The Important Role of Inclusive Schools in Accepting Children with Special Needs in Cluster 2, Cibinong District, Bogor - Sujana, Sujana; Susetyo , Budi; Aprilia, Imas Diana (Angstrom Centre of Education, 2024)
Inclusive schools are places where children with special needs can learn together with other regular children. However, children with special needs are still accompanied by accompanying teachers during teaching and learning activities. The learning system, teaching, curriculum, facilities and infrastructure, as well as the assessment system in inclusive schools will accommodate the needs of children with special needs, so that they can adapt and receive the best possible education. Children with special needs are children who experience delays in development, have medical conditions, mental conditions, and/or certain congenital conditions. They require special attention and handling in order to reach their potential. Children with special needs do not mean they are not smart, talented or incapable. It's just that they have special challenges that most normal children don't face. A School Cluster is an institution/organization as a center for the development of surrounding elementary schools which has the aim of improving the quality of education. The aim of this research is to find out about inclusive schools in accepting children with special needs, especially in cluster 2, Cibinong District, Bogor Regency. The research method used was interviews with school officials, especially school principals, in accepting children with special needs at their school. Interview is a data collection technique through a one-way verbal question and answer process, meaning that questions come from the person interviewing and answers are given by the interviewee.